2001
DOI: 10.1186/bcr377
|View full text |Cite
|
Sign up to set email alerts
|

The CC chemokine RANTES as a potential contributor to breast cancer progression

Abstract: Background: Disruption of the balance between apoptosis and proliferation is considered to be an important factor in the development and progression of tumor. In this study we determined the in vivo cell kinetics along the spectrum of apparently normal epithelium, hyperplasia, preinvasive lesions and invasive carcinoma, in breast tissues affected by fibrocystic changes in which preinvasive and/or invasive lesions developed, as a model of breast carcinogenesis. Materials and method: A total of 32 areas of appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 1 publication
1
25
0
Order By: Relevance
“…2, C and D). Consistent with previous reports that breast tumor cells secrete CCL5 (27,28,(42)(43)(44), our data show that 4T1 conditioned medium contained large amounts of CCL5 and this tumor-derived CCL5 did not mediate the inhibition of host CCL5 expression (Fig. 2, G-I).…”
Section: Discussionsupporting
confidence: 81%
“…2, C and D). Consistent with previous reports that breast tumor cells secrete CCL5 (27,28,(42)(43)(44), our data show that 4T1 conditioned medium contained large amounts of CCL5 and this tumor-derived CCL5 did not mediate the inhibition of host CCL5 expression (Fig. 2, G-I).…”
Section: Discussionsupporting
confidence: 81%
“…In addition, the levels of CCL5 expression were greater than that found in normal epithelial cells, ductal epithelial cells and benign sections. A subsequent study by the same group suggested that the expression of matrix metalloproteinase-9 (MMP9) may be regulated by CCL5, and therefore, CCL5 may play a role in invasion and metastases [3]. Why this chemokine, which is capable of recruiting T cells, did not increase the immunogenicity of these tumors remains unanswered.…”
Section: Introductionmentioning
confidence: 97%
“…Considering all the presented data, we suggest that 30-oxocalenduladiol is a new and specific CCR5 antagonist that exhibits great promise as a bioactive agent for the development of new high active derivatives for treatment of HIV-1 infection, and against biological disorders related to CCR5-mediated cell migration, such as for instance, inflammation, immune response, and tumor cell migration (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57).…”
Section: -Oxo-calenduladiol Is a New Anti-hiv-1 Inhibitormentioning
confidence: 99%